Quirópteros: população e potencial zoonótico em granjas de suínos - Stefanello, Flávia (2016)
This study evaluates the zoonotic potential of bats that use pig farms or their surroundings as lodgings for their colonies in southern Brazil, including rural areas of the municipalities of Camargo/RS, Vila Maria/RS and Concordia/SC also describes the identification of families found (Molossidae and Vespertilionidae) and also species (Molossus molossus, Histiotus velatus and Molossus rufus). As authorized by the national committee (SISBIO / ICMBIO) and the Ethics Committee on Animal Use at the University of Passo Fundo (CEUA-UPF), were captured 80 individuals, and they belong to two families and three species. In the same area blood samples were collected from 37 pigs in the nursery phase. All bats underwent capturing procedures through mist nets, inhalation sedation, transport procedures, anesthesia, identify families/species, collection of blood through cardiac puncture, euthanasia, necropsy, collecting tissues of interest (lung, and liver). After collecting tissues RNA extraction was done using Trizol®, of blood samples from bats and pigs, also bats lungs and liver. It was investigated in blood samples (bats and pigs) and lung (bats) or if there was not the presence of influenza virus by RT-PCR (reverse transcriptase reaction, followed by Polymerase Chain Reaction). Subsequently liver RNA samples were analyzed by nested RT-PCR and RT-PCR assays for hepatitis E virus from the cDNA synthesis obtaining only negative for these agents. The liver RNA samples were also evaluated for the presence of adenovirus by HRM assay. qPCR was performed in such a reaction, we obtained nonspecific amplifications in 35 samples, which were tested again with primers for different species of AdV resulting in 7 positive samples, which were sequenced and are shown in phylogenetic trees.